Web-Based Geographic Information System (GIS) Mapping of SMK Start Up Dara Jingga Student Internship Locations: Sistem Informasi Geografis (SIG) Pemetaan Lokasi PKL Siswa SMK Start Up Dara Jingga Berbasi Web - Rahmad Ramadhani; Lido Sabda Lesmana; Heri Sudibyo (Journal of Vocational Education and Information Technology (JVEIT), 2026)
Web-Based Internship Location Mapping Geographic Information System (GIS) at SMK Start Up Dara Jingga was developed to overcome the limitations of conventional administration using Microsoft Excel. This study aims to design and implement a web-based internship mapping GIS that integrates master data management, spatial visualization of institutions, as well as centralized attendance and daily journal operations. System development utilized the Waterfall model with Unified Modeling Language (UML) diagram modeling. The software was built using PHP with the Laravel framework, MySQL as the relational database, Tailwind CSS for a responsive interface, and Leaflet.js as the interactive digital mapping engine. The results indicate that the system successfully maps the spatial distribution of internship locations. The implementation of radius-based attendance (geofencing) effectively and precisely validates student attendance at internship sites, while the advisor portal simplifies the monitoring of attendance logs and the validation of daily activity journals. Based on Black Box testing across 22 functional scenarios, the system was declared 100% valid with zero operational system errors. This study concludes that this web-based internship location mapping GIS is suitable for implementation and capable of sustainably enhancing the efficiency, accuracy, and transparency of internship administration management at SMK Start Up Dara Jingga.